2014
DOI: 10.1007/s11916-014-0416-5
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Obesity in the Pediatric Population

Abstract: Childhood obesity and headache are both significant health concerns that often have a marked impact both personally and socially, that if not addressed can carry over into adulthood. For many individuals, these effects may be magnified when obesity and headache are seen in conjunction. It is this overlap between obesity and headache in children, as well as similarities in the known mechanism of action for feeding and headache, which led to a suspected association between the two. Unfortunately, although recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Recent studies have reported greater risk of episodic or recurrent migraine or daily chronic headache or tension headache in obese children and adolescents than the normal population [ 128 , 129 ]. Some drugs used for headache and migraine have weight gain as side effect [ 129 ]. Negative lifestyle factors, which may influence the prevalence of recurrent headache, are possible targets for preventive measures [ 130 ].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Recent studies have reported greater risk of episodic or recurrent migraine or daily chronic headache or tension headache in obese children and adolescents than the normal population [ 128 , 129 ]. Some drugs used for headache and migraine have weight gain as side effect [ 129 ]. Negative lifestyle factors, which may influence the prevalence of recurrent headache, are possible targets for preventive measures [ 130 ].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Investigators also have reported an overlay between increased BMI and headaches in children. 97 The association between pain and obesity in elderly individuals is discussed in the literature primarily in the form of narrative review. 98 One study showed that elderly obese individuals (≄70 years, n = 736) had both greater functional disability and an increase in the number of people reporting pain.…”
Section: Obesity and Pain In Children And Elderlymentioning
confidence: 99%
“…The MS that many obese patients suffer can be associated more frequently with behavioural disorders, less neurocognitive development, and lower school performance, especially in areas such as arithmetics and language . At the neurological level, it has been associated with higher rates of episodic or chronic migraine and an increased risk of idiopathic intracranial hypertension that may or may not be associated with a brain pseudotumour . Finally, an aspect that has generated increasing concern in the approach of the paediatric patient with obesity is the impact at the psychological level, since it shows higher rates of depression, anxiety disorders, low self‐esteem, and an increased risk of discrimination and harassment in the school environment.…”
Section: Metabolic and Cardiovascular Comorbiditiesmentioning
confidence: 99%